Effect of New 2-Thioxoimidazolidin-4-one Compounds against Staphylococcus aureus Clinical Strains and Immunological Markers’ Combinations - Hanan Tariq Subhi; Hiwa Ramadhan Fatah; Hanaa Ali Muhammad (Canadian Journal of Infectious Diseases and Medical Microbiology)
Although the structure-activity relationship indicates that the 4-thioxoimidazolidin ring is essential for antibacterial activities and pharmaceutical applications, there were no enough studies on the derivatives of this compound. Evaluating the new hydantoin compounds C5 (3-((2-bromobenzylidene) amino)-2- thioxoimidazolidin-4-one) and C6 (3-((4- methoxybenzylidene) amino)-2-thioxoimidazolidin-4-one) that were prepared against clinical Staphylococcus aureus isolates for antibacterial, antibiofilm, and antihemagglutination activities is the aim of this study. Therefore, the potential clinical resistance of the strains was evaluated by their ability to form biofilms, antibiotic resistance, and agglutinate erythrocytes macroscopically and microscopically; besides, the bacterial biofilm was screened for any association with the patient’s serum immunoglobulin levels and complements. Despite the effective concentration for C5 and C6 compounds, which is ≤ 31.25 μg/ml, the reduction rate is not concentration-dependent; it depends on the molecular docking of the hydantoin compounds. Hence, the effect of the minimal inhibitory concentrations (MICs) is variable. In this study, the results for the compounds (with the concentration of 31.25–62.5 μg/mL for C5 and 62.5–125 μg/mL for C6) significantly manifest the antibacteria, antibiofilm, and antihemagglutination effects against the virulent strains of S. aureus due to the high percentage of biofilm inhibition that was caused by the new hydantoin compounds. Besides, time-kill kinetics studies showed that these compounds pose bactericidal action. Overall, this study revealed that the new hydantoin derivatives have an interesting potential as new antibacterial drugs through the inhibition of bacterial adhesion. The infections of these isolates activate the complement system through the lectin pathway. Nevertheless, these compounds can be improved in order to be used at even lower concentrations.